Dung beetle assemblages on reclaimed coal mines in eMalahleni (South Africa) their environmental associations and tunnelling ability on compacted soils - Dabrowski, Jacqueline (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2017.